Profil Pemecahan Masalah Siswa Pada Konsep Medan Magnet - Totoh Abdul Hakim; Siti Nurdianti Muhajir; Amar Amrullah (Jurnal Kajian Pendidikan IPA, 2026)
This study aims to comprehensively describe students' problem-solving profiles in the magnetic field concept and identify factors influencing students' difficulties in solving physics problems. The research employed a Sequential Explanatory Mixed Method involving 120 eleventh-grade students from two high schools in Garut Regency selected via stratified random sampling. Quantitative data were collected through validated problem-solving tests, while qualitative data were obtained through observations and in-depth interviews to explore thinking strategies and misconceptions. The results indicate that students' problem-solving skills are generally in the medium and low categories. Students demonstrated decent competence in the problem-understanding stage but faced significant obstacles in planning strategies, executing calculations, and evaluating results. Qualitative analysis reveals that students' primary difficulties stem from weak spatial visual representation skills difficulty converting 3D vector diagrams to 2D and fundamental misconceptions regarding magnetic field sources and the application of the right-hand rule. These findings underscore the importance of integrating innovative learning models such as multi-representation-based Problem Based Learning (PBL) and 3D virtual simulations to visualize abstract concepts, thereby reducing misconceptions and effectively enhancing students' problem-solving skills.Keywords: problem-solving skills, magnetic field, physics representation, misconceptions, mixed method.